Epistemological Obstacles to Social Studies Education - Jordi Castellví (Trends in Higher Education)
This article explores the role of discursive practices and epistemological obstacles in shaping educational knowledge and power dynamics within schools. Drawing on critical pedagogy and the works of McLaren, Foucault, Gramsci, and Bachelard, it examines how schools act as sites where hegemonic Discourses are either reproduced or resisted. Discourses, understood as integrated social practices encompassing language, actions, beliefs, and values, deeply influence how students form their social representations of the world. The article highlights the need for educators to challenge traditional curricular theories that prioritize technical knowledge, often presented as neutral, while masking underlying power relations. Through the analysis of Bachelard’s epistemological obstacles, such as simplification, generalization, and depersonalization, the article discusses how these barriers impede students’ ability to critically engage with complex social phenomena. Multiperspectivity is proposed as a key educational approach to foster critical thinking and empower students to challenge social injustices. The discussion calls for systemic educational reforms, emphasizing the importance of teacher training that encourages the identification and questioning of dominant ideologies. By adopting a critical, social justice-oriented pedagogy, educators can help students not only understand but also transform their social realities, promoting an equitable and democratic educational environment.